Examining the patient's satisfaction from Hospital Service Quality using the CRM (Cus-tomer Relationship Management) Model - Hosseini, Mirza Hassan; Mahmoudi Meymand, Mohammad; Heidarvand, Sanaz (Journal of Entrepreneurship, Business and Economics; Vol 3 No 2 (2015), 2015)
This research aims to examine the patient's satisfaction from service quality in Bahrami Hospital considering the CRM model. Generally, six variables of "Physician-Patient Relation", "Nurse-Patient Relation", "Staff-Patient Relation", "Hospital Accountability", "Meeting Patient's Requirements", and "Specialized Performance of the Physicians" have been analyzed in order to measure the impacts of the variables on patient's satisfaction in Bahrami Hospital of Tehran. The statistical population of the research contained the patients (children) who were hospitalized in the Bahrami Children Hospital and/or the parents who were the children's companies. Also, sample size was calculated 196 people based on the Cochran's Formula. This study is an applicable research with a descriptive survey methodology so that the main tool for data gathering is questionnaire. In addition, the Cronbach's Alpha Coefficient for the questionnaire was calculated 0.812 based upon SPSS software. Analyzing the data by SPSS software revealed that all variables except "specialized performance of the physi-cians" had a significant relation with patient's satisfaction. Since the hospital was a training-based medical center, the Pearson correlation coefficient for the variable "specialized performance of the physicians" was calculated 0.137; meanwhile, the meaningfulness amount was obtained 0.056 which is more than the standard limit. Therefore, the aforesaid variable does not have a significant relation with patient's satisfaction. Research paper Reference to this paper should be made as follows: Hossieni, M. H., Meymand, M. M., Heidarvand, S. (2015). “Examining the patient's satisfaction from Hospital Service Quality using the CRM (Cus-tomer Relationship Management) Model: a case study in Bahrami Hospital of Tehran”, Journal of Entrepreneurship, Business and Economics, Vol. 3, No. 2, pp. 16–40.